Tumor Cells Circulate in the Peripheral Blood of All Major Carcinomas but not in Healthy Subjects or Patients With Nonmalignant Diseases - Allard, W. Jeffrey; Matera, Jeri; Miller, M. Craig; Repollet, Madeline; Connelly, Mark C.; Rao, Chandra; Tibbe, Arjan G. J.; Uhr, Jonathan W.; Terstappen, Leon W. M. M. (Clinical cancer research, 2004)
Purpose: The purpose of this study was to determine the accuracy, precision, and linearity of the CellSearch system and evaluate the number of circulating tumor cells (CTCs) per 7.5 mL of blood in healthy subjects, patients with nonmalignant diseases, and patients with a variety of metastatic carcinomas. Experimental Design: The CellSearch system was used to enumerate CTCs in 7.5 mL of blood. Blood samples spiked with cells from tumor cell lines were used to establish analytical accuracy, reproducibility, and linearity. Prevalence of CTCs was determined in blood from 199 patients with nonmalignant diseases, 964 patients with metastatic carcinomas, and 145 healthy donors. Results: Enumeration of spiked tumor cells was linear over the range of 5 to 1,142 cells, with an average recovery of ≥85% at each spike level. Only 1 of the 344 (0.3%) healthy and nonmalignant disease subjects had ≥2 CTCs per 7.5 mL of blood. In 2,183 blood samples from 964 metastatic carcinoma patients, CTCs ranged from 0 to 23,618 CTCs per 7.5 mL (mean, 60 ± 693 CTCs per 7.5 mL), and 36% (781 of 2,183) of the specimens had ≥2 CTCs. Detection of ≥2 CTCs occurred at the following rates: 57% (107 of 188) of prostate cancers, 37% (489 of 1,316) of breast cancers, 37% (20 of 53) of ovarian cancers, 30% (99 of 333) of colorectal cancers, 20% (34 of 168) of lung cancers, and 26% (32 of 125) of other cancers. Conclusions: The CellSearch system can be standardized across multiple laboratories and may be used to determine the clinical utility of CTCs. CTCs are extremely rare in healthy subjects and patients with nonmalignant diseases but present in various metastatic carcinomas with a wide range of frequencies.